2011
DOI: 10.1111/j.1365-2753.2011.01650.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐stroke aphasia prognosis: a review of patient‐related and stroke‐related factors

Abstract: Stroke-related factors, including aphasia severity, lesion site and lesion size, appear most critical to post-stroke aphasia recovery. The findings presented in this review offer clinicians an evidenced-based framework to assist in prediction of post-stroke aphasia recovery patterns and subsequent long-term functional communication outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
146
0
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(174 citation statements)
references
References 54 publications
10
146
0
12
Order By: Relevance
“…Extent of poststroke recovery varies with many patient-related factors (e.g., age at stroke onset, sex, handedness, socioeconomic status) and various stroke-and lesion-related factors (e.g., initial stroke severity, lesion size, stroke subtype, lesion location), but these factors have very limited predictive power for outcome (19)(20)(21)(22)(23)(24). Even good predictors, including initial stroke severity and lesion volume, leave most of the variability in outcome unexplained (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Extent of poststroke recovery varies with many patient-related factors (e.g., age at stroke onset, sex, handedness, socioeconomic status) and various stroke-and lesion-related factors (e.g., initial stroke severity, lesion size, stroke subtype, lesion location), but these factors have very limited predictive power for outcome (19)(20)(21)(22)(23)(24). Even good predictors, including initial stroke severity and lesion volume, leave most of the variability in outcome unexplained (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Predicting aphasia recovery after stroke has received renewed attention in recent literature with papers examining early aphasia diagnosis and the factors believed to affect recovery, whilst providing a description of natural language recovery across time, 2,3 using patient performance on language and cognitive tests to predict therapy gain in the chronic recovery phase 5,8,10 and providing a comprehensive literature review of the variables considered important in aphasia recovery. 11 The ability to more reliably predict improved aphasia outcomes in individual stroke survivors may allow the benefit of limited aphasia rehabilitation services in clinical settings to be maximised. Predictors of aphasia recovery including vascular risk factors, stroke type, infarct volume/size and location, initial aphasia severity and type, age, gender, handedness, level of education, performance on language assessments and intelligence have all been investigated in an attempt to determine both stroke 4,5 and aphasia outcomes [1][2][3][8][9][10] at various points in the recovery journey.…”
Section: Introductionmentioning
confidence: 99%
“…[77][78][79] Other research has found that such characteristics had minimal or mixed effect on recovery from aphasia. 80,81 Evidence is equivocal about the extent to which stroke-related or neurological characteristics such as time post onset, type of aphasia, and location and size of the lesion impact recovery. [81][82][83][84][85] However, it is likely that the interplay of multiple characteristics influences recovery from aphasia.…”
Section: Introductionmentioning
confidence: 99%
“…80,81 Evidence is equivocal about the extent to which stroke-related or neurological characteristics such as time post onset, type of aphasia, and location and size of the lesion impact recovery. [81][82][83][84][85] However, it is likely that the interplay of multiple characteristics influences recovery from aphasia. 85 This article explores whether stroke/neurological characteristics of severity and type of aphasia, and time post onset impact improvements seen after participating in an intensive comprehensive aphasia program.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation